Incentivising and retaining public servants in remote areas: A discrete choice experiment with agricultural extension agents in Ethiopia - Regassa, Mekdim D.; Abate, Gashaw T.; Kubik, Zaneta (John Wiley & Sons, 2021)
Increased deployment of agricultural extension agents (EAs) in rural areas is recommended to spur agricultural productivity and mitigate spatial imbalances in welfare. However, high turnover and low motivation levels of EAs in remote areas pose challenges for equitable service provision and, in some cases, exacerbate geographical welfare disparities. We assess the effectiveness of selected potential interventions to incentivise and retain EAs in remote areas of Ethiopia. To this end, we conducted a choice experiment to elicit the preferences of 761 EAs for job attributes. We apply a random parameters logit model to estimate parameters of interest and to simulate the impact of possible interventions. Our results show that offering education opportunities is by far the most powerful instrument to attract and retain EAs. It increases uptake of the extension job in remote locations by 77 percentage points, which is significantly higher than the effect from doubling current salary levels. EAs also expressed a strong preference for work environments with basic amenities, housing, transportation services, and well-equipped Farmer Training Centres (FTCs). Furthermore, the results from sub-sample analyses show that female EAs are less responsive to pecuniary incentives and are more concerned with the availability of infrastructure and amenities. Current salary levels, years of employment, and location of work are also important sources of heterogeneity in the response of EAs to potential changes.